Morphologic and Morphometric Study of Lungs in Adult Indigenous Peafowl ‎‎(Pavo cristatus) - M AL-Araji, Hanadi; H Mohammed, Hadaf (The Iraqi Journal of Veterinary Medicine, 2023)
Peafowl are a species of bird for which there is limited scientific research, despite the ‎importance of the respiratory system on bird health. This study aimed to provide a detailed ‎anatomical examination and comparative description of the lungs in adult male and female ‎indigenous peafowl (Pavo cristatus) to further our understanding of the respiratory system in ‎this species. Sixteen healthy adult peafowl (8 peacocks and 8 peahens) were obtained from ‎commercial markets in Dyalla, and Baghdad, Iraq. The birds had a mean live weight of 3.5±0.59 kg for females ‎and 3.0±0.39 kg for males. After being anesthetized, the birds were sacrificed by cutting off major ‎blood vessels in the neck. Subsequently, the lungs were carefully dissected and examined to ‎identify their shape, color, position, dimensions, and overall structure. Detailed photographs of ‎the lungs were taken, and various measurements were recorded for each lung in male and ‎female peafowl. The lungs of the peafowl were found to have an elongated, triangular shape, ‎extending from the first to the sixth vertebral ribs. Each lung exhibited two borders (medial and ‎lateral) and three surfaces (vertebral, costal or dorsal, and septal). Notably, the lateral border ‎and dorsal surface of each lung had four deep grooves resulting from the embedding of the ‎second to fifth ribs, which led to the division of the lung into five lobes in both peacocks and ‎peahens. To the best of our knowledge, this study represents the first scientific research on the ‎anatomical features of the lungs in indigenous peafowl. The findings from this study contribute ‎to a better understanding of the lung structure in this bird species, which can be valuable for ‎future studies on avian respiratory physiology and health.‎‎‎